A Critique on the Book The Idea of Literature. From ‘Art for Art’s Sake’ to Writings That Intervene - Hassan Zokhtareh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The introduction of The Idea of Literature. From ‘Art for Art’s Sake’ to Writings That Intervene, the last book by Alexandre Gefen, starts with dedicating the Nobel Prize in Literature to Bob Dylan in 2016 that caused controversial reactions. In Gefen's view, the reason for all these disagreements is the restrictive and aesthetic perception of the concept of literature which has dominated literary critique and theories in academic places from the nineteenth centuriy. In accordance with his previous works, he talks about the revival of literature and the necessity to redefine of the idea of literature, opposing all those who have been shouting for crises of discredit, decay, or even death of contemporary literature, since the beginning of the twenty-first century. In this book, he tries to present a descriptive approach of Contemporary Activist Literature and uses countless references to sources to confront it with autonomous and self-reflective literature in six areas. This essay is first trying to explore the Gefen's functionalist conception of contemporary literature which is very American and then compare it with the ideas of other scholars to find out the implications of Gefen's approach to literature, including the emergence of forms of moral criticism and ideological censorship.